Penggunaan Rekonsturksi Oleh Penyidik Kepolisian Kaitannya dengan Penerapan Asas Praduga Tak Bersalah dalam Kitab Undang-undang Hukum Acara Pidana (KUHAP) (Studi Putusan No: 2390/Pid.B/2017/Pn.Jkt.Brt) - Ayu Agustina; Slamet Riyadi (Program Studi Hukum Universitas Pamulang, 2020)
The investigation stage aims to find and collect evidence from a criminal case. The stages of investigation by police investigators are specifically regulated in the Chief of Police Decree No. Pol: Skep / 1205 / IX / 2000 Regarding Revision of the Guidelines and Technical Guidelines for Criminal Investigation Process. In the investigation stage, there is a reconstruction technique, which is an examination technique by re-demonstrating the way a suspect has committed a criminal act or a witness's recognition with the aim of getting a clear picture of a crime. The principle of presumption of innocence which is owned by the Criminal Procedure Code, by itself provides guidelines for law enforcement officials to apply the breakthrough principle at every level of examination. So that between the use of reconstruction and the application of the presumption of innocence and its relation to the rights of suspects in its juridical review, it is necessary to conduct research. The object of this research is the case decision No.2390 / Pid.B / 2017 / PN.Jkt.Brt. The research method used is a normative juridical research method. The research resulted in an understanding of the position of reconstruction in investigation as an examination technique that is considered important for investigators when a criminal case is difficult and unclear to prove so that reconstruction techniques can be used when the investigator feels the need for it and finds a form of application of the principle of presumption of innocence to the suspect in case decision No. 2390 / Pid.B / 2017 / PN.Jkt.Brt.